THE QUANTIFIED EMPLOYEE: NAVIGATING THE PRIVACY-PERFORMANCE PARADOX IN PEOPLE ANALYTICS - Suwinto; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The increasing adoption of people analytics has transformed how organizations manage and evaluate employee performance, giving rise to the concept of the “quantified employee.” Advances in artificial intelligence and digital monitoring technologies enable organizations to collect and analyze extensive data on employee behavior, productivity, and engagement. While these capabilities offer significant benefits, they also create a tension between performance optimization and employee privacy, known as the privacy–performance paradox. This study examines how organizations can balance data-driven decision-making with ethical considerations related to privacy. Using a narrative literature review and conceptual framework approach, the research synthesizes insights from academic studies, HR reports, and policy documents. The findings indicate that people analytics can enhance productivity, engagement, and workforce optimization, but may also lead to surveillance anxiety, perceived intrusion, and concerns about data misuse. The study highlights the importance of mediating factors such as trust, transparency, and perceived fairness, as well as moderating influences including organizational culture, leadership, and regulatory environments. A conceptual framework is proposed to explain how these factors interact to influence employee acceptance and organizational outcomes. The study concludes that ethical governance and transparent communication are essential for achieving a sustainable balance between privacy and performance.